The socialization and participation of Deaflympians in sport - Foster, R.; Fitzgerald, H.; Stride, A. (Sport in Society: Cultures, Commerce, Media, Politics, 2019)
D/deaf people are often ignored within sports research. This paper centralizes the experiences of four D/deaf athletes who have competed in the Deaflympics and offers some insights about their socialization into sport. The key questions addressed are: (1) What are the key factors enabling D/deaf athletes` involvement and progression in elite D/deaf sport? (2) What are the key challenges D/deaf athletes face when participating and progressing in D/deaf sport? Findings from the interviews suggest that early specialization into sport does not include exposure to Deaf sport. However, the athletes enthusiastically embraced Deaf sport, gaining an immense sense of achievement from these sporting endeavors. Interestingly, this outlook was often tempered because the athletes were aware of the ways in which Deaf sport is valued less than hearing sport. In concluding, we argue that sport practitioners need to promote D/deafness through the merits of `deaf gain` rather than considering D/deafness as negative.